Pengembangan dan Evaluasi Sistem Informasi Peminjaman Barang Berbasis Google Apps Script - Albert Michael Putra Yochanan; Singgih Jatmiko (Computer Journal, 2026)
Item-loan administration in one subdivision still relies on physical handover forms and non-centralized records, making loan status and history difficult to trace. This study developed and evaluated an item-loan information system based on Google Apps Script. The study applied the Waterfall model, covering requirements analysis, design, implementation, testing, and maintenance. Evaluation involved six actual users through total sampling, comprising three officers and three administrators. Functional suitability was assessed using User Acceptance Testing (UAT), while usability was measured using the System Usability Scale (SUS). The UAT score reached 90.56%, with 88.89% for officers and 92.22% for administrators. The mean SUS score was 74.58, categorized as acceptable and good, although three respondents scored below the reference value of 68. Implementation reduced physical-document searches, improved record completeness and loan traceability, and centralized data. The system met functional needs but still requires improvements in initial guidance, activity notifications, stock checks, and handover reporting. The results are limited to six users in one subdivision.